Implementasi Metode Single Moving Average Untuk Prediksi Stok Produsen - Duanna Purnamasari; Endah Ratna Arumi; Ardhin Primadewi (STMIK Budi Darma, 2022)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the national economy such as MSMEs as small-scale food producers. MSMEs as small-scale food producers in the Magelang area are quite diverse, especially in the Deyangan area. To know the amount of daily stock. Keripik